Defibrotide for the management of sinusoidal obstruction syndrome in patients who undergo haemopoietic stem cell transplantation. (November 2016) - Coutsouvelis, John; Avery, Sharon; Dooley, Michael; Kirkpatrick, Carl; Spencer, Andrew
Highlights: Defibrotide is a useful agent in the management of sinusoidal obstruction syndrome (SOS). Most of the published literature describes prophylaxis and treatment in the pediatric population. Various case series and recent trial data describe effectiveness for treatment of SOS in adults. Further research in adults will establish optimal dose and duration in prophylaxis and treatment. Abstract: Sinusoidal obstruction syndrome, previously known as veno-occlusive disease (VOD/SOS), is a complication in patients undergoing haemopoietic stem cell transplantation (HSCT). Severe VOD/SOS, including progression to multi-organ failure, has resulted in a mortality of greater than 80%. Defibrotide's varying pharmacological actions, particularly on endothelial cells, make it is a useful agent to consider for prophylaxis and treatment of VOD/SOS. Barriers to its routine use include the high acquisition cost and the fact that neither the oral or parenteral formulations are licensed products in many countries at this time. This review summarises available literature on the use of defibrotide in the management of VOD/SOS. Publications consist predominantly of single centre cohort studies and case series. Available evidence indicates that defibrotide is effective in the management of VOD/SOS. Using defibrotide prophylaxis should also be considered, especially in the paediatric setting, where there are available results from a large, open label, randomized controlled trial. Patient outcome data from the larger studies and compassionate programs can inform consensus recommendations on dosing regimen and criteria for the treatment of VOD/SOS with defibrotide in the adult population. The reviewed literature indicates an effective and safe dose for treatment is 25 mg/kg/day, continued for at least 14 days or until complete response is achieved. Further studies are required to determine the optimal dose and duration of treatment in both paediatric patients and adults. Recent recommendations and a phase 3 trial using historical controls indicate that defibrotide should be included as a pharmacotherapy option in protocols guiding management of VOD/SOS.